C++ Programming : an object-oriented approach - Forouzan, Behrouz A.; Gilberg, Richard F. (New York; McGraw-Hill, 2020)
"This book compleiments a course designed to teach object-oriented programming using the syntax of the C++ language. It will prepare students for advanced concepts such as data structure and design patterns. Students who have completedA student completing this course will be ready to take on any other object-oriented language course,, a data-structure course, or move into a course about design patterns"--
Introduction to computers and programming languages -- Basics of C++ programming -- Expressions and statements -- Selection -- Repetition -- Functions -- User-defined types: classes -- Arrays -- References, pointers, and memory management -- Strings -- Relationship between classes -- Polymorphism and other issues -- Operator overloading -- Exception handling -- Generic programming: templates -- Input/output streams -- Recursion -- Introduction to data structures -- Standard template library (STL) -- Design patterns.
Includes index.
Keywords: Object-oriented programming (Computer science); C++ (Computer program language)